Genetic analysis in cystic fibrosis using the amplification refractory mutation system (ARMS): the J3.11 MspI polymorphism. Issue 4 (April 1991) - Newton, C R; Summers, C; Heptinstall, L E; Lynch, J R; Finniear, R S; Ogilvie, D; Smith, J C; Markham, A F
Abstract : A new method of genetic analysis has been devised. The method, amplification refractory mutation system (ARMS), has been used to genotype the J3.11 MspI restriction fragment length polymorphism (RFLP) closely linked to cystic fibrosis (CF). The DNA sequence for both alleles of this dimorphism has been used to design ARMS primers. These allow genotyping of DNA isolated from blood, Guthrie cards, and buccal cells.